(untitled) (Papeles, 2023)
This article arises from some questions that were developed within the framework of the teaching task of the Social Work and Daily Life from the Faculty of Social Work of the National University of Entre Ríos (hereinafter FTS-UNER) and the reflections that were framed from there in a Novel Research and Development Project (hereinafter PID Novel) called “The concept of strategy in contemporary debates in Social Work. Its meanings, meanings and implications in professional intervention." Taking as a basis the contributions emanating from the field work of said research, we allow ourselves to analyze the concept of strategy in the framework of training in professional intervention in the academic unit in the that we located the study, we anchor the analysis in the ’84, 2001 and modified 2001 Study plans (hereinafter 2001M). We start by considering the centrality of the epistemological theoretical perspective and the study of the pedagogical political projects that were deployed in order to understand the interpretation process given in a specific historical and institutional context that characterizes the work on the concept of strategy. Finally, we set ourselves the task of analytically reconstructing these keys in light of the curricular structures proposed in social work training at the FTS - UNER.